Association between Body Mass Index and Complete Blood Count Parameters - Hamid, Ghaidaa Rifaat; Khalaf, Rayan Zaidan (International Journal of Statistics in Medical Research, 2025)
Obesity is an abnormal or extraordinary cumulative fat in the body which can lead to health problems. Its prevalence increased worldwide. This study aims to identify the effect of obesity on CBC parameters in obese subjects. Two hundred obese patients of either gender, the mean age was (33.71±2) years, 148 were females (74.4%) and 52 were males (25.6%), each subject submitted to medical history, physical examination, and CBC test. The results of the study revealed that there was a correlation between BMI and CBC parameters, (P value <0.05). This study concluded that there is positive correlation between CBC and BMI (positively correlated, p-value <0.05).